Economics and Business Students' Buying Interest in Eco-Friendly Products: An Analysis of AJZEN's Economic Sociology - Harahap, Rahma Hayati; Simangunsong, Cindy Claudya; Marpaung, Nahwa Zainab (Journal Business Administration: Entrepreneurship and Creative Industry, 2024)
In this era of globalization, consumers are increasingly aware of environmental issues. Consumer behaviour towards environmentally friendly products is a concern in economic sociology. The writing of this article aims to explore the analysis of economics students' behaviour towards environmentally friendly products. This research uses a literature study method, which will involve analysing data from several economics and bussines students in various universities. Environmental awareness, knowledge of environmentally friendly products, economic factors, and social factors are important factors in the decision making of a consumer. Economics and business students as consumers who are aware of environmental issues tend to choose environmentally friendly products. This is of course also influenced by economic factors and consumer social factors. The results of this study provide knowledge in understanding the consumer behaviour of economics and bussines students towards environmentally friendly products. The practical implication of this research is that environmentally friendly product companies targeting economics and bussines students need to consider factors that will influence consumer decision making, including effective and efficient pricing and promotion.